Theoretical Proposal of Taxonomy of Ibero-American Universities from the form of Appointment of the Rectors - Viancos González, Patricio (2020)
The university is faced with tensions and demands resulting from the transformations that society demands. The new public management (NGP) imposes new paradigms as far as university administration is concerned. Concomitantly, the international rankings of universities establish standards and classifications, placing the focus on access to information that should be available to interest groups. This work has been proposed as a central purpose, to describe the ways of appointing the rectors in Latin American universities, with the purpose of elaborating in theoretical terms a taxonomy that allows to differentiate and classify the universities of the region, opening the discussion on what is the most appropriate mechanism to provide the position of the highest university authority. The information used for this study was obtained from a primary source: the database of universities in Latin America; which consists of the Laws, decrees, statutes, regulations of election of authorities among others that regulate 1080 institutions of the Ibero-American region. This information establishes a taxonomy of four types that attempt to simplify and demonstrate the different forms of organization of the institutions. These allow to describe the degree of participation of the interest groups in the process of appointing the rector. The proposed taxonomy confirms the existence of dissimilar mechanisms for appointing the rector and that these are dependent on the type of ownership of the institution.